SAT0482 Undifferentiated connective tissue disease at risk for systemic sclerosis: predictive role of anti-topoisomerase and avascular areas. (12th June 2018) - Riccardi, A.; Messiniti, V.; Fasano, S.; Valentini, G.
Abstract : Background: Undifferentiated connective tissue disease at risk for systemic sclerosis (UCTD-risk-SSc) is a condition characterised by Raynaud's phenomenon and either SSc marker autoantibodies or typical capillaroscopic findings or both, unsatisfying classification criteria for SSc 1 and reported to evolve into definite SSc in about 50% of 60 cases over a 12–102 months follow-up time. 2 We found marker autoantibody positivity to predict the evolution into SSc satisfying 2013 ACR criteria for the disease. 3 Objectives: To investigate in patients followed-up for a longer time if distinct marker autoantibody specificities have a different predictive value. Methods: Sixty-five patients consecutively admitted to a tertiary Rheumatology Unit from November 1 st 2000 to December 31 st 2016 and diagnosed as UCTD-risk-SSc were enrolled in the study. Patients were monitored for a median of 27 months (range 6–144) and were evaluated twice yearly to assess disease progression. Kaplan-Meier curves and the log-rank test were used to analyse differences in fulfilling the criteria for SSc between subsets. Risk prediction was assessed by univariate Cox regression analysis. Results: During follow-up 40/53 marker autoantibody-positive patients (75.5%) versus 3/12 (25%) marker autoantibody negative ones satisfied SSc criteria (p=0.006). Out of them, 11/12 (91.7%) anti-topoisomerase (Scl70) positive versus 29/40 (72.5%) anti-centromere (ACA) positive patients evolved into definite SSc (p=0.04). In univariate analysis, anti-Scl70 positivity increased by 2-fold the risk of a definite SSc outcome (HR 2.1 95% CI 0.9–4.4) with respect to ACA positivity (HR 0.5 95% CI 0.2–1.0) (p=0.05). In addition 3/3 (100%) patients with avascular areas at baseline versus 40/62 (64.5%) with megacapillaries only or no capillaroscopic abnormalities satisfied SSc criteria over a 12–38 months follow-up time (p=0.06). Conclusions: We confirm that autoantibody positivity patients presents a faster evolution. Moreover we first detected an increased HR of Scl-70 versus ACA positivity and a potential role of baseline detected avascular areas. References: [1] Valentini G. Undifferentiated Connective Tissue Disease at risk for systemic sclerosis (SSc) (so far referred to as very early/early SSc or pre-SSc). Autoimmun Rev2015. [2] Valentini G, et al. Early Systemic Sclerosis: Analysis of the Disease Course in Patients With Marker Autoantibody and/or Capillaroscopic Positivity. Arthritis Care Res2014. [3] van den Hoogen F, et al. 2013classification criteria for systemic sclerosis: an American college of rheumatology/European league against rheumatism collaborative initiative. Ann Rheum Dis2013. Disclosure of Interest: None declared